Analysis of The Students’ Argumentative Skills of Senior High School in Covid-19 Pandemic using Problem Based Learning in Static Fluid - Wahdania Eka Putri; Widha Sunarno; Ahmad Marzuki (Jurnal Penelitian Pendidikan IPA, 2021)
This study aims to describe and analyze the students' argumentative skills in the subject of static fluid using the PBL model with the experimental method, after the lesson is given to students. This type of research is descriptive research.The subjects of this study are 34 students of XI MIPA 2 class of SMAN 1 Tanggul. The sampling technique used in this study was simple random sampling. The data was collected by using an essay question consisting of 8 questions which have been adjusted to the indicators of argumentation ability which include; argument evidence, counter argument evidence, refutation evidence, argument justification, counter argument justification, and rebuttal justification. The data analysis of this research used a descriptive approach by calculating the score. The results showed that the average argument evidence indicator is 1.5 with the high category, the counter argument evidence is 1.5 with the high category, the refutable evidence is 1,4 with the high category, the argument justification is 2.1 with the high category, the justification the counter argument is 2.1 with the high category, and the rebuttal justification is 2.1 with the high category. Based on the research that has been done, it can be concluded that the students' argumentative skills on each measured indicator are high